A Contingent Study of DC-to-DC Converters for Sustainable Energy System (International Journal of Innovative Research in Computer Science & Technology, 2022)
There had been significant growth in the  area of renewable energy over the past recent years.  Though there has been great development in sustainable  energy, there is still a long way to go.There are certain  inherent limits to this renewable electricity. Solar and wind  electricity, for example, have an intermittent character. In  comparison to the electric load, the electro-chemical  reaction dynamics in the fuel cell are rather sluggish. This  is incompatible with current electric applications, which  demand continuous voltage and frequency. This research  suggested and tested a novel power circuit to address the  problem of renewable energy's intermittent nature and  poor reaction. The proposed circuit combines a variety of renewable  energy sources with energy storage. The influence of  intermittent nature can be considerably decreased by  combining biofuels have a probabilistic proclivity towards  compensating for one another. The above integration will  improve the entire system's dependability and efficiency.  It may either deliver more energy to the load or absorb  surplus energy from the energy sources, considerably  enhancing the overall system dynamics. We provide electricity for the load using fuel cells, while  solar and wind energy are employed to maintain power.  We're employing buck boost choppers and boost choppers  to adjust the power to the right level. For AC loads, an  inverter converts DC to AC. We use renewable energy in  our project to ensure steady electricity during load. In  MATLAB / Simulink, a software simulation model is  created.
Keywords: DC; MATLAB; Renewable Energy; Simulink